On the number of facets of a 2-neighborly polytope (Моделирование и анализ информационных систем)
A d-polytope P is 2-neighborly if each 2 vertices of P determine an edge. It is conjectured that the number f0(P) of vertices for such polytope does not exceed the number fd-1(P) of facets. The conjecture is separately proved for d < 7 and for f0(P) < d+6.